The petroglyphs of Siberia. These rock drawings along Siberian rivers span a period of perhaps 20.000 years. The indicate connections among ancient peoples living as fas apart as France and Japan. - Okladnikov, Alekseĭ Pavlovich.
1 CD-ROM.